Study of changes in physical and chemical properties of corn during drying and storage process using a modified in-store dryer. Issue 1 (January 2021) - Nurba, D; Agustina, R; Zahara, M
Abstract: In-Store Dryer (ISD) is a dryer with a convective system for grain that also serves as a storage. This research was conducted to study the effect of drying and storage—In-Store Dryer (ISD) on maize's physical and chemical properties. Carried out a 200 kg maize capacity test with 60 cm material stack thickness divided into three layers of piles with a thickness of each layer is 20 cm. Drying occurs at the average drying temperature of 38, 6°C with an average RH environment of 76, 8% and an average RH of dryer space of 52, 2%. Drying for 32 hours using ISD can dry the maize with the pre-drying material's initial moisture content of 20.14% to 13.56%, the right water content for storage. The drying process can affect ash, fat, protein, and maize fiber's physical and chemical composition. The chemical composition on the pre-drying are: Ash content 0, 72%, Fat content 5, 62%, Protein 7, 64% and Fiber 2, 81%. The maize's chemical components undergo post-drying change to become: Ash content 0, 8%, Fat content 5, 11%, Protein 7, 82%, and Fiber 2, 52%. The changing of all components is affected by temperature during the drying process, causing a decrease in water content, affecting other chemical components. The analysis result of maize's nutritional components after drying and storage for 30 days using the In-Store Dryer can maintain maize quality. The analysis result of each component that is the Water Content 11.98%, Ash 1.13%, Fat 5.03%, Protein 8, 05%, and 1.8% fiber, and this is by the provisions of SNI 01-4483-1998 for animal feed.